(untitled) (Research, Society and Development, 2021)
According to the Curriculum Guidelines for Teaching, the study of Sciences has as its object of study the scientific knowledge, associated with the different relationships between human beings and other living beings, in the search for conditions of survival. Therefore, for this knowledge to become effective, it requires a constant relationship between theory and practice providing, through various methodologies, the continuous absorption of knowledge, the present study aims to discover if they are, and how they are used. active methodologies in science teaching by teachers in the city of Angical – PI. What impact does it have on student learning. This article is a qualitative study to investigate methodologies based on data collection, in order to qualify the teaching of Nature Sciences in schools in Angical do Piauí. It is based on information contained, on legal provisions such as BNCC (Common National Curriculum Base), LDB (Law of Guidelines and Bases), Curriculum Guidelines and Parameters, scientific articles and on field research through questionnaires. For this, a field and qualitative research was carried out. In which it was possible to see the need for some teachers to know the active methodologies in order to get more out of them and also the resources available to use them more efficiently. This is also added to the change in the methodological view of the execution of classes and, even, the curiosity to know more active tools and methodologies, although there are major challenges in executing them in classrooms.